The contribution of home-family distress to the presentation difference of childhood obsessive-compulsive disorder across home and school settings - (:unkn) unknown (My University, 2004)
Objective: Further to our recent finding of presentation difference in the symptoms of childhood obsessive-compulsive disorder across home and school settings, and that home is where symptoms predominate, we aimed to find out whether this phenomenon is related to home-family distress. Methods: After the application of CY-BOCS, CGI and a questionnaire consisted of items that served as a comparison of the symptoms across home and school settings, family distress was rated on a 5-point scale (FDM) which reflected home stress factors such as unemployment, parental conflict and care of elderly. Results: Of the 20 children enrolled in the study, 70% were boys and 30% girls who had a mean age of 12.45 ± 3.36. Both CYBOCS and CGI-severity (home and school) scores did not differ significantly within themselves regarding caseness criteria of +3 cutscore on the FDM. Among the data obtained by CY-BOCS and CGI, only Compulsion Subscale of CY-BOCS revealed significant correlation with FDM scores ( r = 0.510, p<0.05). Conclusion: Preliminary data did not support any association between home-family distress and presentation difference. A larger sample is needed to conclude on the contribution of home-family stress factors to the presentation difference in childhood obsessive-compulsive disorder.
Keywords: Adolescent; Child; Family; Obsessive-compulsive disorder; Schools